INTEGRITAS AKADEMIK DAN ETOS BELAJAR ISLAMI - Nabilatun Nafilah; Khairun Syari’ah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Academic integrity is a fundamental element in developing high-quality and character-based education. However, the rapid growth of digital technology and easy access to information have created various challenges, including plagiarism, academic dishonesty, and the misuse of technology in learning processes. In Islamic education, academic integrity can be strengthened through the internalization of an Islamic learning ethos grounded in the values of honesty, trustworthiness, discipline, responsibility, hard work, and worship-oriented learning. This study aims to analyze the concept of academic integrity from the perspective of Islamic education, examine the role of the Islamic learning ethos in strengthening academic integrity, and explain the relevance of the thoughts of Al-Ghazali and Ibn Khaldun to the formation of an integrity-based academic culture. This study employed a qualitative approach using a library research method. The findings indicate that academic integrity in Islam is not merely related to compliance with academic regulations but also represents the implementation of moral and spiritual values derived from Islamic teachings. The Islamic learning ethos plays a significant role in shaping honest, responsible, and ethical academic behavior. Furthermore, the ideas of Al-Ghazali and Ibn Khaldun provide a strong philosophical foundation for strengthening academic integrity through sincerity, proper conduct, perseverance, and respect for the learning process. Therefore, the integration of academic integrity and the Islamic learning ethos can serve as an effective strategy for building an integrity-based academic culture, improving the quality of graduates, and strengthening students’ character in the digital era.